In-Vitro Evaluation of miR-101-5P Effect on Herpes Simplex Virus Replication - Ahmad Piroozmand; Bahar Sadegh-Ehdaei; Mehdi Shabani; Sharareh Moghim; Arezoo Miezaei; Leili Mouhebat (مجله دانشکده پزشکی اصفهان, 2018)
Background: Herpes simplex virus type 1 (HSV-1) is known worldwide for its serious disease and a kind of infection that involves nervous system throughout human lifelong. HSV-1 infection is much more considerable in immunocompromised patients and due to the growing resistance to its main drug, acyclovir, alternative treatments are required. MicroRNAs (miRNAs) regulate host and viral gene expression, post-transcriptionally. One previous study has shown that mir-101-3p expression may play role in HSV-1-infected cells.